SITUAÇÃO DA EDUCAÇÃO COOPERATIVISTA NAS COOPERATIVAS AGROPECUÁRIAS DE MINAS GERAIS - Palloma Rosa Ferreira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
Organizations need to develop strategies that enable learning, enabling the articulation of processes of increasingly effective in developing their organizational culture, supporting their identity and functioning. In Cooperatives this need is recognized from its origins thus called cooperative education is inextricably linked to the development of the same, proclaiming themselves as crucial to the achievement of organizational objectives and is designed for that specific resource. In this perspective, an appropriate cooperative management and development of cooperation require the educative processes to ensure business and social success. For a better understanding of the theme, the general objective is to understand the situation of cooperativist education in the agricultural cooperatives of Minas Gerais and as a specific objective to analyze the role and meaning of cooperative education in the identified agricultural cooperatives. This is an exploratory study in which to raise the empirical data, send questionnaires to 170 agricultural cooperatives to which had access. Thus, we sought to identify the main problems of cooperative education, as perceived by the respondents of cooperatives, as well as what their potential and / or their strengths. It was noticed that in 51 respondents cooperatives, the cooperative education is poorly developed and there is not single definition of what conceptual or thematic that it should encompass. The heterogeneity of the studied organizations allows us to understand the polysemy of the concept of cooperative education and reveal a variety of activities and audiences for which these activities are organized. There was the presence of three areas inside the content that agricultural cooperatives identify as part of the cooperative education: business management, social management (participation of members in management, relationships with partners and promoting the values, principles and cooperative culture) and technical assistance to the cooperative. Thus, we conclude the existence of a field of cooperative education organizations presenting heterogeneity, promoters of training and capacity building, multiplicity of meanings attributed to the concept of cooperative education, public and promoted themes, as well as the procedures and the type of activities included in the processes of training for these agricultural cooperatives organizations.